DESIGN AND DEVELOPMENT OF MEANING-BASED TARANNUM MOBILE APPS MODEL: A PROTOTYPE MODEL FOR “KELAS KHAS KEMAHIRAN MEMBACA DAN MENGHAFAZ AL-QUR’AN” (KKQ) - Hasbullah, Nurul Auji; Fabil, Assoc. Prof. Dr. Norasikin; Yusoff, Prof. Dr. Adnan Mohamed; Azmi, Assoc. Prof. Dr. Ahmad Sanusi (Srawung: Journal of Social Sciences and Humanities, 2022)
The purpose of this paper is to figure out the components and elements for the model thus to design and develop a prototype model of KKQ meaning-based Tarannum mobile app. This study employed document analysis which refers to a systematic procedure for reviewing or evaluating documents whether in printed or electronic materials. This research had systematically reviewed on ten existing Tarannum mobile apps in Google Play Store market to find out those components and elements. From document analysis, matrix analysis is used to analyse what are the components and elements that have in the existing Tarannum mobile apps to be embedded into the prototype model. The findings were analysed in thematic analysis whereby this paper explains each of the components and elements into themes. The result from the finding is a prototype model of KKQ meaning-based Tarannum mobile app was developed. The prototype model consists of six main elements and the meaning-based Tarannum element was added to the model as one of the contributions for this study.